2019
DOI: 10.1051/e3sconf/201913602026
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Barriers to Implement E-Waste Management

Abstract: The increasing of electronic waste (E-waste) is not a new issue in the world and it has been causing trouble throughout the world. This study is conducted to determine and analyze various factors that affect the barriers of E-waste management among the household in Cheras, Malaysia. This study has identified the four independent variables that will affect the implementation of e-waste management among household in Cheras namely lack of awareness, lack of knowledge, lack of cooperation and lack of facilities. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In another statement by the World Health Organization, a study conducted by the Global Environmental Sustainability Programme (GESP) has reported that 17.4% of E-Waste was properly recycled in the recycling facilities has created a positive outcome by withholding approximately 15 million tonnes of carbon dioxide being released to the environment [9]. On the other hand, an innovative method for the development of intelligent E-waste bins, incorporating machine learning algorithms to recognize and classify objects [10][11][12]. The study emphasized the importance of precisely identifying different types of e-waste, such as batteries, circuit boards, and electronic devices.…”
Section: Background Studymentioning
confidence: 99%
“…In another statement by the World Health Organization, a study conducted by the Global Environmental Sustainability Programme (GESP) has reported that 17.4% of E-Waste was properly recycled in the recycling facilities has created a positive outcome by withholding approximately 15 million tonnes of carbon dioxide being released to the environment [9]. On the other hand, an innovative method for the development of intelligent E-waste bins, incorporating machine learning algorithms to recognize and classify objects [10][11][12]. The study emphasized the importance of precisely identifying different types of e-waste, such as batteries, circuit boards, and electronic devices.…”
Section: Background Studymentioning
confidence: 99%